General and individual factor structure of complex preparation of young tennis players of 10-12 years - Kozina, Z.; Yevtyfiieva, I.; Muszkieta, R.; Prusik, K.; Podstawski, R. (Journal of Physical Education and Sport, 2020)
The aim of the study: to determine the general and individual factor structure of the preparedness of young tennis players 10-12 years old. Material and methods. 24 tennis players aged 10-12 years (boys) participated in the study. All athletes gave their consent to conduct examinations, which are performed in the tennis section of Kharkiv. The level of integral readiness of young tennis players of 10-12 years was determined. 61 indicators were analyzed. Comprehensive testing was conducted in September 2018. The selection of tests was carried out according to the program for children and youth sports schools. To determine the place of technical and tactical preparedness in the general structure of training of young athletes on the basis of complex testing was conducted factor analysis by the method of principal components. Results.In the structure of complex training of young athletes were identified 6 main factors: "Special physical and technical-tactical preparedness", "Mobility of the nervous system", "Special endurance", "Short-term memory", "Speed of complex reaction", "Strength nervous system. " The total total variance was 71.3%. The individual factor structure of athletes' readiness was revealed, for which percentages of expression of each factor in each athlete were determined. All athletes have different expressions of different factors, which indicates that there are significant individual differences. This should be reflected in the different features of the game and the need to use individual training programs for young tennis players. Conclusions. For all athletes it is necessary to combine the development of technical and tactical preparedness and special physical with the development of cognitive and psychophysiological functions. This requires the selection of special tools that have a complex effect on physical and psychophysiological and cognitive functions. Such means include the use of special simulators of complex influence on the level of readiness of players and means of visualizing technical and tactical actions.